Study of Left Ventricular Mass in Normal Nepalese Population - Anil, Om Murti; Chaudhary, Nabin; Nikhil, Om Murti; Tiwari, Anu; Singh, Gaurav; Thakur, Abhishek; Rana, Shuva Jung; Khadka, Bijay; Khadka, Binod; Singh, Dipendra (Journal of Nobel Medical College, 2022)
Background: A prospective study was conducted to find distribution of the left ventricular mass in normal adult Nepalese population in order to establish the upper reference limit. Materials and Methods: A total of 100 consecutive male and 100 female participants of age 18 years and above visiting for cardiac checkup were enrolled prospectively in this study. Participants with hypertension, diabetes, obesity and significant cardiovascular disease were excluded. Results: Mean age of study population was 43 years. Mean left ventricular mass in total, male and female population was 127.45±29 gm, 136.48±30.64gm and 118.43±24.24 gm respectively. Mean left ventricular mass index (LVMI) in total, male and female population was 74.52±15.78 gm/m2, 80.04±16.5 gm/m2 and 69.17±13.05 gm/m2 respectively. Left ventricular mass and left ventricular mass index increased with age, Body Mass Index, Systolic and Diastolic Blood Pressure, and were statistically significant (p-value <0.05). Conclusion: Normal left ventricular mass in Nepalese Population was found to be lesser in female compared to male. Left ventricular mass increased with increasing Age and Body Mass Index.